2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28862
|View full text |Cite
|
Sign up to set email alerts
|

Student Outcomes Of Participating in an International Research Experience

Abstract: Lauren is a graduate assistant for Research and Graduate Studies in the College of Engineering at Virginia Tech. She supports the Research and Graduate Studies team by conducting research and assisting on research projects focused on current engineering students and the programs which serve them. Lauren is pursuing her Ph.D. in Educational Research and holds a BA in English from the University of Connecticut and an M.Ed. in Higher Education Administration from the University of South Carolina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Their study more specifically found evidence of pre/post-course increases in efficiency and innovation measures among students completing design projects, and significantly higher efficiency, innovation, and confidence among seniors as compared to first-year students. Still other studies have taken similar approaches to investigating global competency among engineering students (Downey et al, 2006;Jesiek, Haller, & Thompson, 2014;Knight et al 2017;Hatfield et al 2017). For example, the aforementioned study by Jesiek, Haller, & Thompson (2014) used a global engineering scenario prompt to assess engineering students before and after a summer research abroad program, finding evidence of increased cultural sensitivity among the subjects.…”
Section: E Scenario-based Assessment In Engineering Educationmentioning
confidence: 99%
“…Their study more specifically found evidence of pre/post-course increases in efficiency and innovation measures among students completing design projects, and significantly higher efficiency, innovation, and confidence among seniors as compared to first-year students. Still other studies have taken similar approaches to investigating global competency among engineering students (Downey et al, 2006;Jesiek, Haller, & Thompson, 2014;Knight et al 2017;Hatfield et al 2017). For example, the aforementioned study by Jesiek, Haller, & Thompson (2014) used a global engineering scenario prompt to assess engineering students before and after a summer research abroad program, finding evidence of increased cultural sensitivity among the subjects.…”
Section: E Scenario-based Assessment In Engineering Educationmentioning
confidence: 99%
“…Wearable and collaborative robotics as a field presents an additional educational challenge as it is a novel area of robotics and currently requires a collaboration of specific experts from various disciplines around the world. Unfortunately, international collaboration for the education of graduate students is still an understudied area, as mostly research programs are examined (e.g., [24]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to disciplinary and interdisciplinary research experience, it has been reported that participants in REU programs gain skills in independent research, real-world problem solving, critical thinking, motivation to persist in science and engineering, and professional skills, such as communication [12]. Studies of international research experiences have shown similar outcomes, in addition to the global outcomes that are the focus global engineering programs in general [11], [13]. Wheatley et al compared a single global research program across multiple years, and found that adjustments to their orientation seemed to help students achieve greater research focus earlier in the program, resulting in publishable material by the end [14].…”
Section: Literature Reviewmentioning
confidence: 99%